2022
DOI: 10.2478/jcbtp-2022-0014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Role of the Exchange Rate in Monetary Policy Reaction Function of Advanced and Emerging Market Economies

Abstract: The subject of this paper is the evaluation of monetary policy reaction function on panel data of 37 world economies, both advanced and emerging markets, during the period of 1995Q1 – 2018Q3. The paper aims to evaluate the role and importance of the exchange rate in monetary policy reaction function depending on the level of economic development. For this purpose, a relevant set of unbalanced panel data was formed with a balanced relationship between developed and emerging market economies. The methodology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Certainly, we cannot ignore the role of central banks (Fabris and Lazić, 2022) and their unconventional monetary policies in affecting income inequality. In this study, our focus was to establish the link between growth and income inequality.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, we cannot ignore the role of central banks (Fabris and Lazić, 2022) and their unconventional monetary policies in affecting income inequality. In this study, our focus was to establish the link between growth and income inequality.…”
Section: Discussionmentioning
confidence: 99%
“…An expected increase in the CB rate in response to the RER undervaluation was found for Czechia, but not for Hungary, Poland and Romania (Shevchuk, 2020). Recently, Fabris and Lazić (2022) suggested that the central bank reaction to the exchange rate changes is characteristic of the emerging market economies only, not developed ones.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Researchers have investigated many factors that influence monetary policy success or failure, such as inflation targeting, interest rate adjustments, and open market activities. Taylor's key study set the groundwork for the Taylor Rule, providing a systematic way to assess the effectiveness of interest rate changes in monetary policy (Fabris & Lazić, 2022;Levrero, 2023;Orphanides, 2003). Similarly, a study published in the Journal of Monetary Economics studied how liquidity constraints and credit availability affect the effectiveness of monetary policy (Borio & Zhu, 2012;Fabris & Lazić, 2022;Rezende et al, 2021).…”
Section: Literature Review 21 Monetary Policy Effectivenessmentioning
confidence: 99%
“…Taylor's key study set the groundwork for the Taylor Rule, providing a systematic way to assess the effectiveness of interest rate changes in monetary policy (Fabris & Lazić, 2022;Levrero, 2023;Orphanides, 2003). Similarly, a study published in the Journal of Monetary Economics studied how liquidity constraints and credit availability affect the effectiveness of monetary policy (Borio & Zhu, 2012;Fabris & Lazić, 2022;Rezende et al, 2021). The current global context, typified by rapid technological breakthroughs and disruptive financial innovations, warrants a reconsideration of this classic economic idea.…”
Section: Literature Review 21 Monetary Policy Effectivenessmentioning
confidence: 99%